2012
DOI: 10.3851/imp2190
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine plus Adefovir or Telbivudine plus Adefovir for Chronic Hepatitis B Patients with Suboptimal Response to Adefovir

Abstract: Both combination therapies led to a significant decrease in HBV DNA. HBeAg serological outcomes were higher with telbivudine plus ADV combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Another possible explanation is that the emergence of ADVresistant HBV strains following suboptimal response to LAM + ADV might attenuate the superior viral suppressive effect of LdT to that of LAM in these study patients. This is supported by a recent study which reported no differences in virologic and biochemical responses in the comparison of two treatments, LdT + ADV and LAM + ADV, in CHB patients with suboptimal response to ADV monotherapy [44] .…”
Section: Discussionsupporting
confidence: 55%
“…Another possible explanation is that the emergence of ADVresistant HBV strains following suboptimal response to LAM + ADV might attenuate the superior viral suppressive effect of LdT to that of LAM in these study patients. This is supported by a recent study which reported no differences in virologic and biochemical responses in the comparison of two treatments, LdT + ADV and LAM + ADV, in CHB patients with suboptimal response to ADV monotherapy [44] .…”
Section: Discussionsupporting
confidence: 55%
“…Though LAM + ADV has been widely used for rescue therapy in past years for those patients [5,13], patients with sequential LAM and ADV resistance had resistant mutations on the same HBV genome, which anticipated that the combination therapy of LAM + ADV might be unsatisfactory for the CHB patients with genotypic resistance associated with sequential LAM and ADV treatment. Indeed, recent data also showed that the combination therapy of LAM + ADV was not effective and was inferior to ETV containing treatment in suppressing HBV DNA [14], which indicated that ETV based combination therapy would be more superior to the LAM + ADV combination therapy in management of LAM- or ADV- resistant patients. And this superiority of ETV + ADV could be explained by the effect of ETV against ADV resistant mutation and the effect of ADV against LAM resistant mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . also evaluated two different combination therapies in patients with suboptimal response to ADV. Both LAM plus ADV and LdT plus ADV led to notable decrease in viral load, and the rates of BR (76% vs 90%) and VR (81.1% vs 88.6%) were similar between the two groups 12 months after combination treatments.…”
Section: Discussionmentioning
confidence: 99%